2014
DOI: 10.7287/peerj.preprints.660v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mechanisms of intertidal fish coexistence: a model

Abstract: 10Research into the ecology of intertidal fishes of the U.K. appears to be lacking, reportedly due to the 11 mobility and cryptic nature of the more common species. However, some intertidal fishes contribute 12 to the diets of commercially important species such as cod (Gadus morhua), haddock

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Larger body‐sized intertidal fish could also compete for rock pools and exclude smaller fish from the best pools that offer greater opportunities for shelter and feeding (Macieira & Joyeux, 2011; Mahon & Mahon, 1994). Inter‐ and intraspecific relationships can act independently or synergistically, promoting a greater reduction in the abundance of smaller specimens when competition may be high, and a smaller reduction when competition is reduced (Barrett et al, 2014) which could also explain why there were larger individuals of L. pholis on the protected shores. Specimens on protected shores of NES were larger and may have competitively excluded smaller specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Larger body‐sized intertidal fish could also compete for rock pools and exclude smaller fish from the best pools that offer greater opportunities for shelter and feeding (Macieira & Joyeux, 2011; Mahon & Mahon, 1994). Inter‐ and intraspecific relationships can act independently or synergistically, promoting a greater reduction in the abundance of smaller specimens when competition may be high, and a smaller reduction when competition is reduced (Barrett et al, 2014) which could also explain why there were larger individuals of L. pholis on the protected shores. Specimens on protected shores of NES were larger and may have competitively excluded smaller specimens.…”
Section: Discussionmentioning
confidence: 99%
“…octopuses M. defilippi and O. vulgaris,Bennice et al (2021) identified habitat portioning, temporal partitioning, and diet partitioning and the mechanisms for resource portioning. Related to intertidal fish, however,Barrett et al (2014) identified seven mechanisms for the interspecific coexistence: (1) when fish diversity is low, (2) when co-occurrence is minimal, (3) when habitat use is different between species, (4) when shelter/protection are in high abundance, (5) when resources are such that co-occurring fishes prey upon food items other than fish, (6) when resources are varied enough that competition for prey items is reduced, and (7) when there is a difference intargeted prey items. Applying these mechanisms to the current work, it could be considered that coexistence is maintained and promoted as octopus diversity is low (two resident species) and that co-occurrence is minimal (and is reducing).…”
mentioning
confidence: 99%